IMPLEMENTASI TINDAK TUTUR ASERTIF PADA SIDANG PENGADILAN MILITER III-13 KOTA MADIUN: TINJAUAN PRAGMATIK - Mufadhdhal, Dzakyy Ridha (Universitas Sebelas Maret, 2021)
Military court trials are known to contain elements of the speech act process. This study aims to describe the form of speech acts applied by the social components at the trial of the Madiun Military Court. The theory used to describe the phenomenon is the illocutionary speech act theory which was established by John R. Searle and focused on the category of assertive speech acts. The method applied in this research is qualitative method. The data collection technique was carried out by participants observation through the observation and note-taking technique equipped with a recording technique. The data from this research are speech acts performed by the social components at the trial of the Military Court III-13 Madiun. The data analysis was carried out by conducting descriptions based on the classifications made by Searle regarding illocutionary speech acts and speech application points detailed by Vanderveken and Rahardi. The results of the study are presented with the assertive speech act classification variables which include speech acts (1) stating, (2) suggesting, (3) bragging, (4) complaining, (5) claiming, (6) giving testimony, (7) reporting, and (8) speculating. This research is essential from the perspective of pragmatic studies to analyze the influence of individual interests in a trial by looking at it from the perspective of assertive speech acts. In a broader sense, the research results are expected to be implemented in understanding a speech act in a more complex social area.